Martian Manhunter. Volume 1, The epiphany - Williams, Rob (Robert Glyndwr) (DC Comics, 2016)
For some time now, Martian Manhunter has been lost in our world. An alien in every aspect, he has struggled to find his place even after joining the Justice League of America, Justice League United and Stormwatch. Now his past has come back to haunt him. As an alien invasion threatens to destroy the world, the Martian Manhunter must make the ultimate sacrifice.